2017
DOI: 10.1097/mat.0000000000000539
|View full text |Cite
|
Sign up to set email alerts
|

Incidence of Cannula-Associated Deep Vein Thrombosis After Veno-Venous Extracorporeal Membrane Oxygenation

Abstract: Limited literature regarding the incidence of cannula-associated deep vein thrombosis (CaDVT) after veno-venous extracorporeal membrane oxygenation (VV ECMO) exists. The purpose of this study was to identify the incidence of post decannulation CaDVT and identify any associated risk factors. Forty-eight patients were admitted between August 2014 and January 2016 to the Lung Rescue Unit were included in the study. Protocolized anticoagulation levels (partial thromboplastin time [PTT] 45-55 seconds) and routine p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
52
3

Year Published

2018
2018
2022
2022

Publication Types

Select...
4
4

Relationship

2
6

Authors

Journals

citations
Cited by 78 publications
(59 citation statements)
references
References 15 publications
4
52
3
Order By: Relevance
“…The incidence of CaDVT varies between 18.1% and 85.4% according to diagnostic methods (7,10,11), and recently we have reported a prevalence of 71.4% when using exclusively a CT scan for diagnosis (8) which is consistent with the present results. When compared with the influenza group, we found a higher prevalence of CaDVT in the SARS-CoV-2 group, but the difference was not statistically significant, probably due to a lack of power (84.6% vs 60%, respectively).…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…The incidence of CaDVT varies between 18.1% and 85.4% according to diagnostic methods (7,10,11), and recently we have reported a prevalence of 71.4% when using exclusively a CT scan for diagnosis (8) which is consistent with the present results. When compared with the influenza group, we found a higher prevalence of CaDVT in the SARS-CoV-2 group, but the difference was not statistically significant, probably due to a lack of power (84.6% vs 60%, respectively).…”
Section: Discussionsupporting
confidence: 93%
“…Therefore, close monitoring of anticoagulation with a higher target than usual, especially in patients with risk factors for thrombosis and/or elevated d-dimer, is suggested (4). During venovenous ECMO, the occurrence of venous thromboembolism has been studied, with an incidence of up to 85% of cases (7). In SARS-CoV-2 patients requiring venovenous ECMO, the prevalence of venous thromboembolism events has only been investigated using ultrasonography.…”
mentioning
confidence: 99%
“…13 Cannula associated DVT is also common occurring in up to 85% of ECMO patients. 5 There are no animal studies confirming that VV ECMO cannulas cause venous congestion in the brain, but it is reasonable to assume that they increase cerebral venous pressure, as this phenomenon has been reported in patients with much smaller central venous catheters (8F), particularly in cases of bilateral internal jugular vein cannualtion. 14 Based on these observations, we hypothesized that large dual lumen VV ECMO cannulas would increase the risk for ICH and in fact our study data confirmed this.…”
Section: Discussionmentioning
confidence: 99%
“…Further, a large number of patients develop cannula associated deep venous thrombosis during ECMO, which may contribute to intracranial venous hypertension. 5 Both smaller and large dual lumen VV ECMO cannulas are currently in use. At the present time, it remains unclear which cannula size is optimal for the "average" adult VV ECMO patient.…”
Section: Introductionmentioning
confidence: 99%
“…An incidence of DVT after VV-ECMO with systematic screening as high as 85% has been described in patients on VV-ECMO. 46 The development of this complication does not seem to be associated with the level of anticoagulation achieved during ECMO but could be higher with larger dual-lumen cannulas. 47,48 The use of VV circuits allows clinicians to avoid the complications related to arterial cannulation, such as arterial bleeding, limb ischemia, and pseudoaneurysm formation.…”
Section: Complications From Extracorporeal Life Supportmentioning
confidence: 99%